Strategi Parents' Strategy in Developing Adolescents' Attitudes in Using the Internet in Muara Megang Musi Rawas Village: Attitudes in Using the Internet - kamsi, nurlila; Yesi Arikarani; Siti Nabilah Rifdah Azzahra; Pipit Malani (SYAIKHONA: Jurnal Magister Pendidikan Agama Islam, 2024)
Social media is a place to share information and communication for Indonesian people. Things that cannot be separated from life and almost every moment cannot be separated from smartphones. Smartphones have positive and negative impacts that are felt by the public. Apart from that, technology can also make work easier, but the negative impacts of technology are the rise of kidnapping, pornography, rape, drugs and prostitution transactions. This research aims to analyze parents' strategies for cultivating wise attitudes in using the internet in Muara Megang Musi Rawas village from research. This research uses a qualitative method with an approach based on facts in the field. We conducted this research, making the researcher the instrument who will later conduct interviews, observations and documentation as the basis for this research. that poor use of the internet has a very negative impact on the daily character of teenagers and that is why parents need to educate their children well in using the internet, including providing education about the bad impacts of bad actions and supervising their use of the internet in everyday life. . By providing education to teenagers about how to use the internet safely and responsibly. This includes explaining dangers such as cyberbullying, online fraud, and inappropriate content. Parents can also set limits on internet use, this includes time limits, the type of content that can be accessed, and the devices that can be used and provide examples for teenagers in using the internet where parents must show teenagers how to use the internet in a positive and positive way. productive. The author recommends that in the future more in-depth follow-up research be conducted regarding how to make the internet a media for motivating teenagers to develop their potential.